Standing Soldiers, Kneeling Slaves : Race, War, and Monument in Nineteenth-Century America - Savage, Kirk, 1958- (Book collections on Project MUSE., 1997)
Here Kirk Savage shows how the greatest era of monument building in American history arose amidst struggles over race, gender, and collective memory. As men and women North and South fought to define the war's legacy in monumental art, they reshaped the cultural landscape of American nationalism.